Independent work of students. Methodical manual for independent work of students for the 6th course - Kirsanova, E. V.; Sukhomlinova, I. Ye.; Yeryomina, A. K.; Sokolovskaya, I. A.; Fedorchenko, R. A.; Kutsak, A. V.; Sharavara, L. P.; Volkova, Yu. V.; Кірсанова, Олена Валентинівна; Сухомлінова, Ірина Євгенівна; Єрьоміна, Алла Кузьмівна; Соколовська, Ірина Анатоліївна; et al. (Zaporozhye : ZSMU, 2017)
Methodical manual compiled by the department of general hygiene and ecology of Zaporozhye State Medical University in accordance with the curriculum for students on 6 course of medical faculty.